Survival: life in earth's toughest habitats - Taylor, Barbara (Dorling Kindersley London, 2002)
A great non-fiction alternative to middle grade readers -- perfect for school projects or reading for fun. Full-color, fun, and crammed with cool facts, DK's Secret Worlds take a fresh look at familiar subjects with brilliant results! Kids ages 9 and up can delve into a wide range of subjects from nature, history, and science for researching school projects, satisfying a curious appetite, or just for the love of reading. Tried-and-tested Web sites and a Mega-reference section are just two of the innovative features that will keep kids and parents coming back for more.